2021
DOI: 10.1186/s12935-021-02040-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic outcome of ‘type 2 diabetes mellitus and breast cancer’ association pivots on hypoxia-hyperglycemia axis

Abstract: Type 2 diabetes mellitus and breast cancer are complex, chronic, heterogeneous, and multi-factorial diseases; with common risk factors including but not limited to diet, obesity, and age. They also share mutually inclusive phenotypic features such as the metabolic deregulations resulting from hyperglycemia, hypoxic conditions and hormonal imbalances. Although, the association between diabetes and cancer has long been speculated; however, the exact molecular nature of this link remains to be fully elucidated. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 188 publications
(169 reference statements)
0
19
0
3
Order By: Relevance
“…For instance, diabetes in premenopausal women has been correlated with a major risk of developing a breast tumor, mostly the aggressive subtype named triple-negative breast cancer (TNBC) [ 105 , 106 ]. In addition, previous studies have indicated that breast cancer mortality associated with distant metastasis is elevated in those patients with co-occurring low-grade chronic inflammatory conditions, such as obesity and T2DM [ 7 , 107 , 108 , 109 , 110 ]. Of note, the IL-8 serum levels were found markedly increased in the T2DM patients in relation to the healthy subjects, and positively correlated with worse metabolic control and an inflammatory state [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, diabetes in premenopausal women has been correlated with a major risk of developing a breast tumor, mostly the aggressive subtype named triple-negative breast cancer (TNBC) [ 105 , 106 ]. In addition, previous studies have indicated that breast cancer mortality associated with distant metastasis is elevated in those patients with co-occurring low-grade chronic inflammatory conditions, such as obesity and T2DM [ 7 , 107 , 108 , 109 , 110 ]. Of note, the IL-8 serum levels were found markedly increased in the T2DM patients in relation to the healthy subjects, and positively correlated with worse metabolic control and an inflammatory state [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of T2DM and breast cancer was shown by the hypoxia-independent stabilization of HIF-1α via the insulin–PI3K–AKT, MAPK/ERK, IL-1, and NF-κB pathways. Subsequent HIF-1α-mediated events and the induction of glucose transporter GLUT1, glycogen synthase kinase, E-cadherin, and matrix metalloproteinases lead to epithelial–mesenchymal transition, the “entrance-hall” of cancer [ 133 ]. The risks and factors involved in cancer development in T2DM patients have been recently reviewed elsewhere [ 127 , 134 ].…”
Section: Clinical Complications Of T2dmmentioning
confidence: 99%
“…According to the recent studies, type two diabetes is a distinct risk factor for the progression of different cancers [8,9]. In addition, cancers that are related to one type of diabetes may not be linked to the other, such as breast cancer, which is mainly linked to type 2 diabetes and not type 1 diabetes [10]. The most common type of malignancy in women is breast cancer (23 percent of all malignancies) [11], and it ranks second overall when both sexes are taken into account [12].…”
Section: Introductionmentioning
confidence: 99%